Conjugal union : what marriage is and why it matters - Lee, Patrick, 1952-; George, Robert P. (New York, NY : Cambridge University Press, 2014)
"During a recent day-time television talk show a young woman was informed that her husband had offered her best friend 500 dollars to have sex with him. Needless to say, the young woman (the wife) became very angry and she (along with the talk-show host and most of the audience present) viewed this act as an egregious betrayal"--
Includes bibliographical references and index.
Keywords: Marriage; Marriage